Geração de termos com violação de simetria de Lorentz à temperatura finita - Freire, Wellington Romero Serafim (2015)
In this thesis, we investigated the generation of the higher derivative Chern-Simons term, as well as the ether-like term, both at finite temperature. We also examined the question of the large gauge invariance, with respect to the Chern-Simons term and the hight derivative one. We observed that the coefficient of the Chern-Simons term vanishes, when we taken into account the limit of high temperature. This happens to occur also for the other high derivative terms. With respects to the Chern-Simons term, we observed that the action of the Chern-Simons term and the high derivative one are invariant under the large gauge transformation. For this, we calculated the exactly effective action, however, for a specific gauge choice. Finally, with respects to the ether-like term, we observed that the calculation at finite temperature is ambiguous, as well as it is observed for the calculation at zero temperature.